Structural and Optical Characterization of Zinc Oxide Films Prepared By Two Stage; Spin Coating and Hydrothermal Process - Dangol, Laxmi; Joshi, Leela Pradhan (Journal of Institute of Science and Technology, 2016)
Thin films of Zinc Oxide (ZnO) of average thickness 364 nm were deposited on glass substrates via hydrothermal process using a mixture of 25 mM aqueous solutions of zinc nitrate and hexamethylenetetramine at a constant temperature of 75 ± 5°C. The structure of ZnO film was analyzed by using X-ray diffraction (XRD). Our result showed that ZnO film is of polycrystalline nature with preferential orientation along (002) perpendicular to the substrate. Average crystallite size of prepared ZnO film was found to be 18 nm. The Scanning Electron Microscope (SEM) image clearly showed the growth of nano-plate structure with an average thickness and breadth of 90 nm and 390 nm respectively. The band gap of ZnO was determined from transmittance spectrum captured in the visible wavelength. The calculated value of direct band gap was 3.24 eV. Journal of Institute of Science and Technology Vol. 21, No. 1, 2016, page: 61-64